Efektivitas Latihan Senam Jantung Sehat untuk Menurunkan Kadar Lemak pada Ibu-Ibu PKK Desa Sukowarno Kabupaten Musi Rawas - Pujiati Pujiati; Muhammad Suhdy; Hengky Remora. (e-SPORT: Jurnal Pendidikan Jasmani, Kesehatan dan Rekreasi, 2022)
This study aims to determine the decrease in fat levels in PKK women in Sukowarno Village after being given a Healthy Heart Gymnastics exercise. The research method used was quasi-experimental. The data collection technique in this study used a skinfold calipers body fat percentage test. Data analysis technique with normality test. Based on the survey results, the magnitude of t count is 12.63 and t table 2.056 with a significant 5% (α = 0.05) with degrees of freedom dk = n-1 where n is the number of student data as many as 27 mothers. Suppose the value of t count > t table. Then the hypothesis is accepted so that the average results of fat levels in PKK women in Sukowarno village after being given healthy heart exercise are less than the post-test average value. In conclusion, healthy heart exercise effectively reduces fat levels in PKK women in Sukowarno village, Musi Rawas district. Keywords: Decrease, fat content, healthy heart exercise,